2022
DOI: 10.1038/s41598-022-08480-x
|View full text |Cite
|
Sign up to set email alerts
|

Spirometry has added value over electrodermal activity as a physiological marker of mental load in male subjects

Abstract: The objective distinction of different types of mental demands as well as their intensity is relevant for research and practical application but poses a challenge for established physiological methods. We investigated whether respiratory gases (oxygen uptake and carbon dioxide output) are suitable to distinguish between emotional stress and cognitive load. To this end, we compared the application of spirometry with an established procedure, namely electrodermal activity (EDA). Our results indicate that electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…Aydemir et al found that photoplethysmograph (PPG) can replace the traditional subjective techniques for human heart rate detection in practice 26 . Neukirchen et al used vital capacity equipment to measure the respiratory gases of subjects and found that respiratory gases are sensitive and specific to cognitive load 27 . The respiratory gases have the advantage of predicting cognitive performance and self-reported emotional states and can detect and distinguish different mental needs.…”
Section: Backgroundsmentioning
confidence: 99%
“…Aydemir et al found that photoplethysmograph (PPG) can replace the traditional subjective techniques for human heart rate detection in practice 26 . Neukirchen et al used vital capacity equipment to measure the respiratory gases of subjects and found that respiratory gases are sensitive and specific to cognitive load 27 . The respiratory gases have the advantage of predicting cognitive performance and self-reported emotional states and can detect and distinguish different mental needs.…”
Section: Backgroundsmentioning
confidence: 99%
“…Considering the complexity and impact of respiration, reducing its study to a single parameter, such as respiratory rate, seems to be insufficient, being necessary more variables. These parameters are based on respiratory gases, particularly oxygen uptake (VO2) and carbon dioxide output (VCO2), which are sensitive to cognitive load and can be influenced by emotional processes [257]. Other aspects such as respiration VOLUME 11, 2023 rate, velocity, and depth, should be considered due to their alteration in different mental states and diseases.…”
Section: E Respiratory Activitymentioning
confidence: 99%
“…There are several types of spirometers that measure the volume of air in different ways such as using pressure difference, ultrasonics, water, or a wright peal flowmeter spirometer. This technique can be useful for determining VO2 and VCO2 levels [257], [259].…”
Section: E Respiratory Activitymentioning
confidence: 99%